An Evolution Model for Remote and Virtual Labs - Correia, Raul Cordeiro (2021)
A graphical model that describes and anticipates the evolution of remote and virtual laboratory systems and networks is proposed. eThe model was built considering the “remote past” and the “recent past”, to make a projection about the future evolution, on each of the development lines that persist today. The verification of the proposed model considers some remote and virtual labs networks and systems that have existed and/or still exist today translating their story through graphs that show the evolution of the system affected by different variables, states, flows, processes, and results defined on the dynamic model and also a specific sub-model for the kernel of the main model.